FACTORS INFLUENCING THE INTENTION TO PARTICIPATE IN DISCARDED FACE MASK MANAGEMENT AMONG URBAN RESIDENTS - Karil, Vayolla Syakirah; Nastiti, Anindrya (UI Scholars Hub, 2024)
Massive mask usage during the COVID-19 pandemic has been causing increased mask waste problem. Improper mask management can spread virus in the environment. Proper mask waste management behaviours must be investigated to better understand the underlying factors. Studies have focused on mask waste management in Indonesia, but none have used a comprehensive behavioural framework. This study integrates the Theory of Planned behaviour (TPB) and the Norm Activation Model (NAM) aiming to determine the factors that influence the intentions of Pekanbaru’s residents in managing mask waste. The survey involved 384 respondents selected through a systematic cluster random sampling. The data was analysed with PLS-SEM to verify the model. We hypothesised that awareness of consequences, the ascription of responsibility, subjective and personal norms, attitudes, and perceived behavioural control positively affect behaviour. Attitudes (p < 0.05, t = 2.681), personal norms (p < 0.05, t = 6.708), and perceived behavioral control (p < 0.05, t = 5.846) are also positively and significantly related to mask waste management intention. Awareness of consequences has a significant indirect effect on mask waste management intention through attitude (p < 0.05, t = 2.638), and the highest indirect effects are through ascription of responsibility and personal norms (p < 0.05, t = 4.885). The consequence of awareness, ascription of responsibility, and personal norms are essential elements in enhancing motivations for taking responsibility and participating in household waste management. Demographics such as age and monthly expenses significantly affect mask waste management intentions. This work offers a novel integration of TPB and NAM, which enhances research on the behavioural intents of household mask waste management. Based on the results, the policy implications of how to motivate society to sort waste were discussed, and research limitations were indicated.